Pelabelan Harmonis Ganjil pada Kelas Graf Baru Hasil Operasi Cartesian Product - Fery Firmansah; Muhammad Ridlo Yuwono (Jurnal Matematika MANTIK, 2017)
Graph class which has the characteristic of odd harmonious labeling is called as odd harmonious graph. Net graph is a graph which is gained by using operation Cartesian product of two line graphs. The construction of snake-net graph is inspired by the definition of snake graph replacing the round graph to net graph. In this paper, the study will show that snake-net graph fulfill the characteristic of odd harmonious graph in such a way snake-net graph is the odd harmonious graph. In the end of this paper, it is also shown that the union of snake-net graph is also called as the odd harmonious graph.